Eva's treetop festival - Elliott, Rebecca (2015)
Having a Bloomtastic Festival at school to celebrate spring is a great idea--but Eva Wingdale, a young owl, discovers that it is also a lot of work, and there is nothing wrong with asking her friends for help.
Keywords: Owls -- Juvenile fiction; Festivals -- Juvenile fiction; Diaries -- Juvenile fiction; Elementary schools -- Juvenile fiction; Help-seeking behavior -- Juvenile fiction; Friendship -- Juvenile fiction; Owls -- Fiction; Festivals -- Fiction; Schools -- Fiction; Helpfulness -- Fiction; Friendship -- Fiction; Diaries -- Fiction